Effects of variation in length and diameter of acoustic couplers on the frequency characteristics of hearing aids - Chandra P (Journal of All India Institute of Speech and Hearing, 1970)
The acoustic coupler is a device, made out of plast~ic, that links the hearing aid receiver to the ear. It serves the dual function of chanellising the sound into the ear canal and supporting the receiver to fit snugly on the ear. Thus, it is essential for all types of air conduction hearing aids.